Sub-Hourly Variations of Wind Shear in the Mesosphere-Lower Thermosphere as Observed by the China Meteor Radar Chain - Chi Long; Tao Yu; Jian Zhang; Xiangxiang Yan; Na Yang; Jin Wang; Chunliang Xia; Yu Liang; Hailun Ye (Remote Sensing, 2024)
Wind shear has important implications for Kelvin–Helmholtz instability (KHI) and gravity waves (GWs) in the mesosphere–lower thermosphere (MLT) region where its momentum transport process is dominated by short-period (<1 h) GWs. However, the sub-hourly variation in wind shear is still not well quantified. This study aims to improve current understanding of vertical wind shear by analyzing multi-year meteor radar measurements at the Mohe (MH, 53.5°N, 122.3°E), Beijing (BJ, 40.3<semantics>°N</semantics>, 116.2<semantics>°E</semantics>), Wuhan (WH, 30.5<semantics>°N</semantics>, 114.6<semantics>°E</semantics>), and Fuke (FK, 19.5°N, 109.1°E) stations in China. The wind field is estimated by a new algorithm, e.g., the damped least squares fitting. Taking the wind shear estimated by normal products as a criterion, the shear produced by the new algorithm has more statistical convergence as compared to the traditional algorithm, e.g., the least squares fitting. Therefore, we argue that the 10 min DLSA wind probably produces a more reasonable vertical shear. Both intensive wind shears and GW kinetic energy can be simultaneously captured during the 0600–1600 UTs of May at MH and during the 1300–2400 UTs of March at FK, possibly implying that the up-propagation of GWs could contribute to the production of large wind shears. The sub-hourly variation in wind shears is potentially valuable for understanding the interrelationship between shear (or KHI) and GWs.